2017
DOI: 10.1016/j.str.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into BLM Recognition by TopBP1

Abstract: SUMMARY Topoisomerase IIβ binding protein 1 (TopBP1) is a critical protein-protein interaction hub in DNA replication checkpoint control. It was proposed that TopBP1 BRCT5 interacts with Bloom syndrome helicase (BLM) to regulate genome stability through either phospho-Ser304 or phospho-Ser338 of BLM. Here we show that TopBP1 BRCT5 specifically interacts with the BLM region surrounding pSer304, not pSer338. Our crystal structure of TopBP1 BRCT4/5 bound to BLM reveals recognition of pSer304 by a conserved pSer-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…In addition, amino acids N-terminal of this SQ motif closely resemble the TOPBP1 BRCT4-5 interaction site in BLM ( Supplementary Fig. 9d) 37,38 .…”
Section: Wtmentioning
confidence: 86%
“…In addition, amino acids N-terminal of this SQ motif closely resemble the TOPBP1 BRCT4-5 interaction site in BLM ( Supplementary Fig. 9d) 37,38 .…”
Section: Wtmentioning
confidence: 86%
“…Interestingly, experiments using the B3/4-BLM Human chimera suggest a conserved role for the STR-Dpb11 interaction in regulating recombination. Indeed, BLM and TOPBP1 were reported to interact in human cells (Blackford et al, 2015; Sun et al, 2017), although it is unclear whether ATR plays any role in promoting that interaction, and if the BLM-TOPBP1 interaction affects HR.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent work suggested that a single BRCT domain (BRCT5) mediates the TopBP1-BLM interaction and that two different phosphorylated serine sites in BLM, pSer304 (Blackford et al, 2015) and pSer338 (Wang et al, 2013), could be the targets of BRCT5. In this issue of Structure , Sun et al (2017) show that TopBP1 BRCT5 recognizes BLM pSer304 but not pSer338. Consistent with this finding, two acidic and four hydrophobic residues preceding Ser304 are evolutionarily conserved, while residues surrounding Ser338 are not conserved.…”
mentioning
confidence: 91%
“…Overall, with the demonstration that a single BRCT domain (TopBP1 BRCT5) can bind a phosphorylated target (BLM helicase) with a micromolar range K d , on par with the typical affinities measured for tandem BRCT repeats, the study of Sun et al (2017) deepens our understanding of phosphotarget recognition by BRCT domains. This work also strongly suggests that a similar mechanism is at play in the interaction of TopBP1 with 53BP1, a key DNA double-strand break repair protein whose association with TopBP1 may contribute to its DNA damage checkpoint function (Qu et al, 2013).…”
mentioning
confidence: 96%
See 1 more Smart Citation